A synthetic data-driven machine learning approach for athlete performance attenuation prediction - Cordeiro, M. C.; Cathain, C. O.; Daly, L.; Kelly, D. T.; Rodrigues, T. B. (Frontiers in Sports and Active Living, 2025)
Introduction: Athlete performance monitoring is effective for optimizing training strategies and preventing injuries. However, applying machine learning (ML) frameworks to this domain remains challenging due to data scarcity limitations. This study extends previous research by evaluating Tabular Variational Autoencoders (TVAE) for generating synthetic data to predict performance attenuation in Gaelic football athletes.